STUDENTS’ PARLIAMENT TO BE PROMOTED TO THE ASEAN LEVEL - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 19 December 2015 – The setting up of the Students’ Consultative Council at Universiti Sains Malaysia (DPP USM) has led to the establishment of the Youth Parliament and was then extended to the Malaysia Students’ Parliament.